Depression, anxiety and stress in homemakers during COVID-19 pandemic - Hardika, Jelang; Rinaldi, Martaria Rizky (Faculty of Psychology, Universitas Negeri Yogyakarta, 2024)
The COVID-19 pandemic has had a significant impact worldwide, affecting various aspects of life. One prominent group affected by these circumstances are homemakers